COMPENSATION'S IMPACT ON EMPLOYEE ENGAGEMENT AND PERFORMANCE - Kiki Farida Ferine; Andriya Risdwiyanto; Yogi Nurfauzi; Kraugusteeliana Kraugusteeliana (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
Employee performance is one of the determining factors in a company's performance. Compensation, job satisfaction, and employee engagement are all factors that can influence employee performance. A coffee shop is a popular type of business in recent years. The rise in coffee shops and domestic coffee consumption over the last three years demonstrates this. The purpose of this study is to examine the effect of compensation on employee engagement and how it affects employees who work in high-end coffee shops. This study employs quantitative methods for causality research. The sampling technique used was accidental sampling, with 89 respondents from Tanaka coffee shops in Bandung Regency. The Structural Equation Model was used for statistical analysis in this study (SEM). According to the study's findings, compensation has a significant and positive effect on employee engagement because a higher salary increases employee engagement. Employee engagement has a significant and positive effect on employee performance because the employee pays more attention to the company; their performance will improve. Payment, on the other hand, has no significant impact on employee performance because low pay does not cause employees to perform poorly. Managers of coffee shops must pay attention to employee compensation and welfare in order to increase employee engagement and performance. on the other hand, it has no significant impact on employee performance because low pay does not cause employees to perform poorly. Managers of coffee shops must pay attention to employee compensation and welfare in order to increase employee engagement and performance. on the other hand, it has no significant impact on employee performance because low pay does not cause employees to perform poorly. Managers of coffee shops must pay attention to employee compensation and welfare in order to increase employee engagement and performance.